2017
DOI: 10.1103/physrevlett.119.015701
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing Entropy and Enthalpy Fluctuations to Drive Crystallization in Atomistic Simulations

Abstract: Crystallization is a process of great practical relevance in which rare but crucial fluctuations lead to the formation of a solid phase starting from the liquid. As in all first order first transitions, there is an interplay between enthalpy and entropy. Based on this idea, in order to drive crystallization in molecular simulations, we introduce two collective variables, one enthalpic and the other entropic. Defined in this way, these collective variables do not prejudge the structure into which the system is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 32 publications
(37 reference statements)
1
104
0
Order By: Relevance
“…For a discussion of S 2 we refer the reader to Ref. 11. This has been a simple proof of principle to show that crystal structures, even the ones that are stabilized by entropy 12 , can be predicted.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…For a discussion of S 2 we refer the reader to Ref. 11. This has been a simple proof of principle to show that crystal structures, even the ones that are stabilized by entropy 12 , can be predicted.…”
mentioning
confidence: 95%
“…If one is interested in discovering new polymorphs this approach defeats the purpose. Recently, however, we have shown that in simple systems this can be circumvented by using as collective variable surrogates of enthalpy and entropy 11 . The idea is to mimic what happens in a real system in which there is a trade off between entropy and enthalpy.…”
mentioning
confidence: 99%
“…A large fraction of these methods depends on the definition of collective variables (CVs). Typical examples are umbrella sampling [2][3][4][5], metadynamics [6][7][8][9] and variationally enhanced sampling [10]. The efficiency of these simulations depends very much on the quality of the CV, and hence the finding and improving of CVs is the object of intense investigations [11].…”
Section: Introductionmentioning
confidence: 99%
“…The calculations of the fingerprint were done using a development version of PLUMED 2 41 . The RDF is calculated using a kernel density estimation of the radial distribution function 6,7 . Which for a Gaussian kernel is:…”
Section: Methodsmentioning
confidence: 99%